PEMANFAATAN NOTEBOOKLM DALAM PENGEMBANGAN MEDIA VIDEO KETELADANAN UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN PAI DI MADRASAH TSANAWIYAH - Syamsoeri, Rahmawati; Berlian, Zainal; Baharuddin, Baharuddin (STKIP Subang, 2026)
The development of digital technology has driven changes in the learning process across various levels of education, including Islamic Religious Education (PAI). However, in practice, PAI learning is still often dominated by conventional methods such as lectures, memorization, and assignments, resulting in low student participation in the learning process. This study aims to analyze the phenomenon of the use of conventional teaching methods in PAI learning in Grade VII at State Islamic Junior High School 1 Palembang and to propose a solution through training teachers in the use of exemplary video media. This research employs a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation studies involving teachers of Arabic, Qur’an Hadith, Fiqh, Islamic Cultural History (SKI), and Aqidah Akhlak. The results show that the dominance of lecture-based methods leads to low student participation in the learning process. The use of exemplary video media has been proven to enhance students’ learning motivation, improve their understanding of the material, and provide concrete examples in instilling Islamic values. Training teachers in the use of video media also plays a significant role in improving their pedagogical competence and digital literacy in developing innovative and contextual learning.Thus, the utilization of exemplary video media can serve as an innovative strategy to improve the quality of Islamic Religious Education learning in schools.